Principle and Pragmatism in the Liberation Struggle - Mabutho Shangaze (African Journal of Political Science)
This book zeroes into the life of Selby Msimang a politician and activist of the early 20th century South Africa. Msimang’s life is thrust against the social and political backdrop of South Africa beginning in the middle 19th century in colonial Natal. The historical context of conquest and colonialism is an important setting for this life story. It is this background of black oppression and struggles that Msimang navigates as he dedicates his life to the fight against black oppression and his own personal tribulations as a man and political activist. Whilst the author does not overtly express the linkages between the protagonist’s life at micro level of social interaction and the macro level historical institutions that structure and shape Msimang’s journey, the connectedness is quite glaring.